Biofilm formation by clinically isolated Staphylococcus Aureus from India - Alasthimannahalli Gangadhara Triveni; Mendem Suresh Kumar; Chavadi Manjunath; Channappa T Shivannavar; Subhaschandra M Gaddad (Journal of Infection in Developing Countries)
Introduction: Staphylococcal biofilms are prominent cause for acute and chronic infection both in hospital and community settings across the world. Current study explores biofilm formation by Staphylococcus aureus isolates from clinical samples by different methods.